Psychoeducation of Academic Procrastination in Undergraduate Students - Setiyono, Gilang Agus; Paramita, Riyangka; Hartini, Nurul (Psikostudia : Jurnal Psikologi, 2023)
Academic procrastination is the tendency always or almost always to postpone work on academic assignments and always or almost always experience disturbing anxiety related to the academic procrastination carried out. Academic procrastination negatively impacts a student's life in the academic, physical and social fields. Therefore, it is necessary to implement psychoeducation to prevent and intervene in academic procrastination in students, especially those at an advanced level. This psychoeducational activity aims to map the level of procrastination of advanced students at the ABC Department, XYZ Faculty, X University and increase students' understanding of academic procrastination. The subjects of this research were 138 Semester 6 students at the ABC Department, XYZ Faculty, X University. The method used is a survey using the Aitken Procrastination Inventory procrastination measuring instrument. Changes in student understanding were measured through pre-test and post-testpost-test, then analyzed using the T-test. From the results of observations, it is known that as many as 4 students (2.9%) were at the "very low" level of procrastination, 38 people (27.5%) were at the "low" level, 61 people (44.2%) were at the "moderate" level. , 31 people (22.5%) were at the "high" level and 4 people (2.9%) were at the "very high" level. The T-test results showed that there was a significant difference (P value = 0.001) in the mean pre-test (7.67) and post-test (8.20) scores. These results show an increase in knowledge before and after psychoeducation.Prokrastinasi akademik merupakan kecenderungan untuk selalu atau hampir selalu menunda pengerjaan tugas-tugas akademik dan selalu atau hampir selalu mengalami kecemasan yang mengganggu terkait dengan prokrastinasi akademik yang dilakukan. Prokrastinasi akademik memiliki berbagai dampak negatif dalam kehidupan seorang mahasiswa, baik dalam bidang akademik, fisik dan sosial. Oleh karena itu, perlu dilaksanakan psikoedukasi sebagai upaya pencegahan dan intervensi prokrastinasi akademik pada mahasiswa terutama yang telah berada pada tingkat lanjut. Tujuan dari kegiatan psikoedukasi ini adalah untuk memetakan tingkat prokrastinasi mahasiswa tingkat lanjut pada Jurusan ABC, Fakultas XYZ, Universitas X dan meningkatkan pemahaman mahasiswa mengenai prokrastinasi akademik. Subjek penelitian ini adalah mahasiswa Semester 6 pada Jurusan ABC, Fakultas XYZ, Universitas X sebanyak 138 orang. Metode yang digunakan adalah survey dengan menggunakan instrumen ukur prokrastinasi Aitken Procrastination Inventory. Perubahan pemahaman mahasiswa diukur melalui pre-test dan post-test yang kemudian dianalisa dengan menggunakan T-test. Dari hasil pengamatan diketahui bahwa sebanyak 4 orang (2.9%) mahasiswa yang berada pada tingkatan prokrastinasi “very low”, 38 orang (27,5%) pada tingkatan “low”, 61 orang (44,2%) pada tingkatan “moderate”, 31 orang (22,5%) pada tingkatan “high” dan 4 orang (2,9%) pada tingkatan “very high”. Hasil uji T menunjukkan adanya perbedaan yang signifikan (nilai P = 0.001) pada rerata nilai pre-test (7,67) dan post-test (8.20) . Hasil ini menunjukkan adanya peningkatan pengetahuan sebelum dan sesudah dilakukan psikoedukasi.